2006
DOI: 10.1016/j.cub.2006.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Chronic jet-lag increases mortality in aged mice

Abstract: Despite the fact that trans-meridian travel and shift work are commonplace in our 24/7 society, few controlled studies have addressed the health effects of repeated phase shifts of the biological clock. Shift work [1] and chronic jet-lag [2] reduce mental acuity and increase the risk of a number of medical problems including cancer, digestive diseases including peptic ulcers, and sleep disorders. Some of these problems become more severe with the number of years on the job, the result either of cumulative dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
261
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(277 citation statements)
references
References 10 publications
10
261
2
4
Order By: Relevance
“…51,52 Due to circadian rhythms, time of day is an important consideration when performing research on living subjects. 53 Jurgen Aschoff, one of the founders of chronobiology, introduced the concept of "zeitgeber [time-giver] time" in the 1960s to simplify the reporting of results that were impacted by circadian-linked changes. Using this system, the time at which daylight emerges or the lights turn on in the laboratory is referred to as zeitgeber time zero (ZT0).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…51,52 Due to circadian rhythms, time of day is an important consideration when performing research on living subjects. 53 Jurgen Aschoff, one of the founders of chronobiology, introduced the concept of "zeitgeber [time-giver] time" in the 1960s to simplify the reporting of results that were impacted by circadian-linked changes. Using this system, the time at which daylight emerges or the lights turn on in the laboratory is referred to as zeitgeber time zero (ZT0).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…26 Moreover, advances in the light-dark transitions hasten the death of aged mice. 27 In humans, such advances can take place after flights crossing time zones or shift work schedules. The precise mechanism of action underlying this hazardous effect is not stressrelated but links more likely to sleep deprivation or disruption of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The ramifications of this desynchronization for mental and physical health are not fully understood, although numerous lines of evidence are emerging that link defects in circadian timing with negative health outcomes (2,3). Animal models have shown that chronic circadian disruption can alter mortality rates in tau mutant hamsters (4) and in aged mice (5). The current obesity epidemic in Western societies has also occurred hand-inhand with a gradual decrease in sleep time and sleep quality (6), and although largely correlative, a potential causal link is plausible.…”
mentioning
confidence: 99%